The emerging era of pharmacogenomics: current successes, future potential, and challenges. (9th May 2014) - Lee, J.W.; Aminkeng, F.; Bhavsar, A.P.; Shaw, K.; Carleton, B.C.; Hayden, M.R.; Ross, C.J.D.
<x xml:space="preserve">Abstract</x> The vast range of genetic diversity contributes to a wonderful array of human traits and characteristics. Unfortunately, a consequence of this genetic diversity is large variability in drug response between people, meaning that no single medication is safe and effective in everyone. The debilitating and sometimes deadly consequences of adverse drug reactions (ADRs) are a major and unmet problem of modern medicine. Pharmacogenomics can uncover associations between genetic variation and drug safety and has the potential to predict ADRs in individual patients. Here we review pharmacogenomic successes leading to changes in clinical practice, as well as clinical areas probably to be impacted by pharmacogenomics in the near future. We also discuss some of the challenges, and potential solutions, that remain for the implementation of pharmacogenomic testing into clinical practice for the significant improvement of drug safety.